1993
DOI: 10.1085/jgp.102.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Pre-steady-state charge translocation in NaK-ATPase from eel electric organ.

Abstract: Time-resolved measurements of charge translocation and phosphorylation kinetics during the pre-steady state of the NaK-ATPase reaction cycle are presented. NaK-ATPase-containing microsomes prepared from the electric organ of Electrophorus electricus were adsorbed to planar lipid bilayers for investigation of charge translocation, while rapid acid quenching was used to study the concomitant enzymatic partial reactions involved in phosphoenzyme formation. To facilitate comparison of these data, conditions were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
92
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 56 publications
18
92
1
Order By: Relevance
“…The activation energy of s 1 , E a , which represents the rising phase of the current transient, was 98 kJ/mol in the standard solution, whereas an E a of 65 kJ/mol was obtained for s 2 characterizing the falling phase. These values are in good agreement with previously reported results of measurements performed in the same model system under similar conditions (Fendler et al 1993), where the activation energies were reported to be 101 kJ/mol and 68 kJ/mol, respectively. The amplitude of short circuit current decreased and its kinetics was slowed down in the presence of choline iodide (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The activation energy of s 1 , E a , which represents the rising phase of the current transient, was 98 kJ/mol in the standard solution, whereas an E a of 65 kJ/mol was obtained for s 2 characterizing the falling phase. These values are in good agreement with previously reported results of measurements performed in the same model system under similar conditions (Fendler et al 1993), where the activation energies were reported to be 101 kJ/mol and 68 kJ/mol, respectively. The amplitude of short circuit current decreased and its kinetics was slowed down in the presence of choline iodide (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The conformation transition P-E 1 /P-E 2 is supposed to be the slowest step of the ion transfer (Sokolov et al 1998b). Although this interpretation is most widely adopted (Holmgren et al 2000;Sokolov et al 1998a;Wuddel and Apell 1995), there is an alternative point of view that the conformation transition controls the rising phase of the current signal (Fendler et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric location of the binding site of the third sodium ion means that the cytoplasmic access channel for this ion should be rather shallow with a dielectric coefficient of 0.25 [24]. Therefore, electric signals associated with the transport in the cytoplasmic access channel evaded detection for a long time.…”
Section: Electrogenic Transport Of Sodium Ions Inmentioning
confidence: 99%
“…Electrogenic ion transport in the Na + ,K + -ATPase can be studied in a system consisting of a lipid bilayer (BLM) and small membrane fragments that contain ion-pumps and adsorb to the bilayer surface in an oriented manner [15,[24][25][26][27][28]. The BLM serves as capacitive electrode transmitting the electrical signals that arise due to electrogenic transport in the membrane fragments to an external detection circuit.…”
Section: Electrogenic Transport Of Sodium Ions Inmentioning
confidence: 99%
See 1 more Smart Citation